Cyclic Polyester Formation with an [OSSO]‐Type Iron(III) Catalyst. Issue 1 (23rd October 2019) - Impemba, Salvatore; Della Monica, Francesco; Grassi, Alfonso; Capacchione, Carmine; Milione, Stefano
Abstract: The efficient formation of cyclic polyesters from the ring‐opening polymerization of lactide, ϵ‐caprolactone, and β‐butyrolactone catalyzed by a 1, 4‐dithiabutanedyl‐2, 2′‐bis(4, 6‐dicumylphenol) [OSSO]‐FeCl complex activated with cyclohexene oxide was achieved. The catalyst was very active (initial turnover frequency up to 2718 h −1 ), robust, and worked with a monomer/Fe ratio up to 10 000. The formation of cyclic polymers was supported by using high‐resolution matrix‐assisted laser desorption ionization (MALDI) MS, and the average ring size (≈5 kDa for cyclic polylactide) independent of the reaction conditions. A monometallic ring‐opening polymerization/cyclization mechanism was proposed from the results of a kinetic investigation. Abstract : Squaring the cycle : Cyclic polyesters are prepared selectively from cyclic esters by a ring‐opening polymerization/cyclization reaction catalyzed by a highly active (initial turnover frequency=2700 h −1 ) and robust (turnover number=10 000) [OSSO]‐type Fe III complex.